(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Self and social location are being reconfig-ured in contemporary autobiographical writings. This article reflects on autobiog-raphies such as Devaki Jain’s ‘The Brass Notebook: A Memoir’ and Wandana Sonal-kar’s, ‘Why I am not a Hindu woman: A personal Story. Questions of social and po-litical are probed differently in both auto-biographies. What are the tropes and ways through which it addresses the complex spaces of subjectivity, identity and poli-tics? Is there any distinct way of engaging with the past and the present? Thus, the paper looks at aforementioned autobiog-raphies through diverse, interdisciplinary approaches.